Lake Batur water quality analysis through Storet method as an effort to control lake water pollution - Widyasari, Ni Putu Setya; Wesnawa, I Gede Astra; Atmaja, Dewa Made (International Journal Labs, 2024)
This study aims to analyze the quality of Lake Batur which aims to maintain the preservation of Lake Batur as a form of sustainable tourism in Bangli Regency. In this study, there are three sample points, namely in Songan Village, Toya Bungkah and Kedisan Village. In this study, it will be analyzed through 11 parameters analyzed, namely temperature, odor, taste, color, pH, nitrate, BOD, DO, total phosphate, total coliform and fecal coliform. In this test, the method used is the STORET method, and in the analysis of the strategy used for pollution control using the SWOT method. Based on the results of the STORET calculation, the sample in Songan Village is included in the category of light pollution with a value of -4, the sample of Kedisan Village all indicators meet the Class 3 Water Quality Standard, and at the sample point in Toya Bungkah is included in the category of light pollution with a value of -8. The indicator that has a value exceeding the Class III Water Quality Standard, namely at the sample location of Songan and Toya Bungkah Villages, is the BOD level. So that the recommended strategy for its management based on SWOT analysis is to optimize the Strengths and Opportunities owned by Lake Batur, namely developing tourism around the lake which is based on sustainable development and in line with regular lake rejuvenation efforts carried out to maintain the balance of lake water quality by the community and the surrounding government.